The unequal burden of the Covid-19 pandemic: Capturing racial/ethnic disparities in US cause-specific mortality. (March 2022) - Luck, Anneliese N.; Preston, Samuel H.; Elo, Irma T.; Stokes, Andrew C.
Abstract: Despite a growing body of literature focused on racial/ethnic disparities in Covid-19 mortality, few previous studies have examined the pandemic's impact on 2020 cause-specific mortality by race and ethnicity. This paper documents changes in mortality by underlying cause of death and race/ethnicity between 2019 and 2020. Using age-standardized death rates, we attribute changes for Black, Hispanic, and White populations to various underlying causes of death and show how these racial and ethnic patterns vary by age and sex. We find that although Covid-19 death rates in 2020 were highest in the Hispanic community, Black individuals faced the largest increase in all-cause mortality between 2019 and 2020. Exceptionally large increases in mortality from heart disease, diabetes, and external causes of death accounted for the adverse trend in all-cause mortality within the Black population. Within Black and White populations, percentage increases in all-cause mortality were similar for men and women, as well as for ages 25–64 and 65+. Among the Hispanic population, however, percentage increases in mortality were greatest for working-aged men. These findings reveal that the overall impact of the pandemic on racial/ethnic disparities in mortality was much larger than that captured by official Covid-19 death counts alone. Highlights: Covid-19 death rates in 2020 were highest in the Hispanic community. Covid-19 mortality was especially marked among working-age Hispanic men. All-cause mortality increases between 2019 and 2020 were greatest for Black adults. Over a third of Black all-cause mortality increase was unexplained by Covid-19. Black non-Covid-19 mortality increases were primarily driven by heart disease, diabetes, and external causes.